Do firms with standalone risk management committee have better performance than those with combined committee? - Awang, Naqiah; Razali, Fatin Adilah; Abu Talib, Shafinaz Lyana (GADING Journal for the Social Sciences, 2023)
Malaysian Code of Corporate Governance 2017 has introduced the Step-Up Practice 9.3 to set up a focused, standalone Risk Management Committee among large, listed firms to combat risk issues in minimizing business losses caused by changes in the business landscape at unprecedented speed. However, the formation of this standalone committee as part of the governance monitoring mechanism is quite expensive making listed firms carefully evaluate its effectiveness. To provide insight to the practitioners and regulators, this study aims to test if there is any significant difference in firm performance between firms with a standalone Risk Management Committee and those with a traditional combined committee. Secondary data were adopted from the top 50 largest listed firm’s annual reports for 2018 and 2019. DataStream was used to gather data on firm performance. Man-Whitney U Test was run using SPSS 28 as a nonparametric statistical. Results uncovered a significant difference in firm performance between firms with a standalone Risk Management Committee and firms with a combined committee. However, combined committee firms were reported to have better performance. These findings provide insight into the Malaysian risk governance structure in responding to the Malaysian Code of Corporate Governance 2017. The regulator could use these findings to design a better risk mechanism for promoting a prosperous financial market